Pengaruh Motivasi Terhadap Kinerja Pegawai - Asthenu, Jean Rosalina (Jurnal Ilmiah Poli Bisnis, 2024)
The West Seram Regency Agriculture Service is tasked with helping carry out government activities in the agricultural sector. There are still several problems where employees lack motivation from the leadership. The aim of the research was to analyze the influence of motivation on the performance of SBB Regency Agriculture Service employees. Using descriptive analysis and simple linear regression. The population are 33 employees of the SBB District Agriculture Service. This research used a saturated sample where the sample are 32 employees of the SBB Regency Agriculture Service, not including the head office. Descriptive analysis shows that employee motivation has an average value of 2.99 which is interpreted as quite good, while employee performance has an average value of 3.28 which is interpreted as quite good. The results show that motivation has a positive and significant effect on the performance of SBB Regency Agriculture Service Employees. So, the SBB District Agriculture Service must increase employee motivation by paying attention to work performance, and work facilities. Employee performance can be improved by paying attention to indicators of quality, quantity, responsibility, cooperation and initiative. Keywords: Motivation, Employee Performance, Cooperation